Efek Antimikotik Minyak Mimba (Azadirachta indica) terhadap Dermatofita - Estri, Siti Aminah Tri Susilo; Habib, Inayati; Suswardana, Suswardana; Siswati, Agnes Sri (Universitas Muhammadiyah Yogyakarta, 2006)
Recently, natural substances have been much developed for antimycotic medicine, such as neem tree that can be found in Indonesia. Oilfrom the neem seed has been proved to have antimycotic effect on non-dermatophytic fungi. The aim of this research was to determine antimycotic effects of neem oil on T. mentagrophytes, E. floccusum and M. gypseum by means of dilution method.This research utilized a simple experimental method. One ml of water and 1 ml of casein yeast glucose were placed into 10 tubes. One ml of pure neem oil was introduced into tube I and the liquids were mixed. Afterwards, 1 ml of solution from tube I was added into tube II. One ml of the solution from tube II was then added into tube III, and so forth up to tube X. Subsequently, 1 ml of dermatophytic suspension (106 cell/ml) was introduced into each tube. The growth of dermatophyte colony was examined on day 5 to 7, after being incubated at room temperature.Results of this research showed that on day 5, T. mentagrophytes began to appear in tube IV (neem oil concentration of 3,12%), while E. floccusum and M. gypseum appeared in tube III (6,25%). On day 7, all colonies began to appear in tube II; therefore, the minimal inhibitory concentration was 12,5%). Neem oil started to have antimycotic effect on T. mentagrophytes, E. floccusum and M. gypseum at a concentration of 6,25%.Akhir-akhir ini banyak dikembangkan bahan alami sebagai antimikotik, antara lain pohon mimba yang banyak terdapat di Indonesia Minyak dari bij i mimba terbukti mempunyai efek antimikotik terhadap berbagai jamur non dermatofita. Tujuan penelitian ini adalah untuk mengetahui efek antimikotik minyak mimba terhadap T. mentagrophytes, E. floccusum dan M. gypseum dengan metode dilusi.Penelitian menggunakan metode eksperimental sederhana. Pada 10 tabung dimasukkan 1 ml aqua dan lml casein yeast glucose. Pada tabung I ditambahkan 1 ml minyak mimba murni dan dicampur. Pada tabung ke II ditambahkan 1 ml larutan dari tabung I, begitu seterusnya sampai tabung ke X. Selanjutnya pada masing-masing tabung ditambahkan 1 ml suspensi dermatofita 106 sel/ml. Pertumbuhan koloni dermatofita dinilai pada hari ke 5-7 setelah diinkubasi pada suhu kamar.Hasil penelitian menunjukkan bahwa pertumbuhan koloni T. mentagrophytes pada hari ke-5 mulai tampak pada tabung ke-4 (konsentrasi 3,12%), koloni E. floccusum dan M. gypseum pada tabung ke-3 (konsentrasi 6,25%). Pada hari ke-7 semua koloni mulai tampak pada tabung ke-3, sehingga kadar hambat minimal pada konsentrasi 12,5%. Efek antimikotik minyak mimba terhadap T mentagrophytes, E. floccusum dan M. gypseum mulai tampak pada konsentrasi 6,25%.